(untitled) (Світ фінансів, 2017)
Орлів М. С. Бюджетування витрат в нафтогазовій геологорозвідці. Окреслено проблеми бюджетування операційних витрат геологорозвідувальних підприємств(наприкладі дочірніх підприємств Національної акціонерної компанії “Надра України”), запропоновано вдосконалення його методики. Розкрито питання забезпечення гнучкості бюджетів, ефективності бюджетного контролю та аналізу. Orliv M. Budgeting of expenses in the oil and gas geological survey. The problems in the budgeting of expenses were researched as per the operational expenses of the geological enterprises (on the example of subsidiary companies of the National Stock Company “Nadra of Ukraine”), the improvement of its methodology was suggested. The issue of providing the flexibility for budgets was reviewed as well as the effectiveness of the budget monitoring, control and analysis.